Processo de avaliação do INEP/MEC de bibliotecas universitárias pertencentes às instituições de educação superior privadas de Belo Horizonte/MG - Joelma Gualberto de Oliveira (2010)
This paper analyzes the process of external evaluation of university libraries sponsored by INEP / MEC due to the need for greater understanding of the external and internal variables for these information units. External variables are composed by the scenario of universityeducation in Brazil, which recorded a large increase in the number of private university education institutions and, consequently, supply of places in university education. As the internal scene is the way the university library is linked with the activities developed in teaching undergraduate and postgraduate (if applicable) in private university education institutions. Given this reality, we sought to achieve the goal of examining the academic libraries of private university education institutions based on the understanding that the evaluators of the Ministry of Education, the representatives of private university educationinstitutions and the librarians of the private institutions have of the evaluation process. This analysis aimed to obtain the opinion of these agents against the role that these units of information play in the external assessment promoted by INEP / MEC, as well as in the teaching-learning process and the importance they have on organizational structure of these institutions. The methodology used in field research was the analysis of the Collective Subject Discourse, which is based on analysis of the views of social actors and focus on building a collective discourse that represents the social actors concerned. The results indicate that theuniversity library is still in very fragile position in the private university education institutions, there is great disparity between the concepts presented for this unit of information. It was also concluded that a great subjectivity on the part of evaluators is present in the process of external evaluation. It can also be said that the understanding of what is valued in university libraries is not uniform and that the insertion of the unit of information in the teaching-learning process is incipient.